ChemInform Abstract: A Convenient Catalytic Procedure for Direct Synthesis of Arylselanyl Anilines. Issue 6 (21st January 2016) - Yu, Chen; Shi, Hongwei; Zhu, Min; Yan, Jie
Abstract: A novel process for the regioselective selanylation of the para‐position of anilines with diphenyl and dibenzyl diselenide under oxidizing conditions is presented.